Epidural electrical stimulation of the cervical spinal cord opposes opioid‐induced respiratory depression. (31st May 2022) - Huang, Ruyi; Worrell, Jason; Garner, Eric; Wang, Stephanie; Homsey, Tali; Xu, Bo; Galer, Erika L.; Zhou, Yan; Tavakol, Sherwin; Daneshvar, Meelod; Le, Timothy; Vinters, Harry V.; et al.
Abstract : Abstract: Opioid overdose suppresses brainstem respiratory circuits, causes apnoea and may result in death. Epidural electrical stimulation (EES) at the cervical spinal cord facilitated motor activity in rodents and humans, and we hypothesized that EES of the cervical spinal cord could antagonize opioid‐induced respiratory depression in humans. Eighteen patients requiring surgical access to the dorsal surface of the spinal cord between C2 and C7 received EES or sham stimulation for up to 90 s at 5 or 30 Hz during complete (OFF‐State) or partial suppression (ON‐State) of respiration induced by remifentanil. During the ON‐State, 30 Hz EES at C4 and 5 Hz EES at C3/4 increased tidal volume and decreased the end‐tidal carbon dioxide level compared to pre‐stimulation control levels. EES of 5 Hz at C5 and C7 increased respiratory frequency compared to pre‐stimulation control levels. In the OFF‐State, 30 Hz cervical EES at C3/4 terminated apnoea and induced rhythmic breathing. In cadaveric tissue obtained from a brain bank, more neurons expressed both the neurokinin 1 receptor (NK1R) and somatostatin (SST) in the cervical spinal levels responsive to EES (C3/4, C6 and C7) compared to a region non‐responsive to EES (C2). Thus, the capacity of cervical EES to oppose opioid depression of respiration may be mediated by NK1R+/SST+ neurons in the dorsal cervical spinal cord. This study provides proof of principle that cervical EES may provide a novel therapeutic approach to augment respiratory activity when the neural function of the central respiratory circuits is compromised by opioids or other pathological conditions. Key points: Epidural electrical stimulation (EES) using an implanted spinal cord stimulator (SCS) is an FDA‐approved method to manage chronic pain. We tested the hypothesis that cervical EES facilitates respiration during administration of opioids in 18 human subjects who were treated with low‐dose remifentanil that suppressed respiration (ON‐State) or high‐dose remifentanil that completely inhibited breathing (OFF‐State) during the course of cervical surgery. Dorsal cervical EES of the spinal cord augmented the respiratory tidal volume or increased the respiratory frequency, and the response to EES varied as a function of the stimulation frequency (5 or 30 Hz) and the cervical level stimulated (C2–C7). Short, continuous cervical EES restored a cyclic breathing pattern (eupnoea) in the OFF‐State, suggesting that cervical EES reversed the opioid‐induced respiratory depression. These findings add to our understanding of respiratory pattern modulation and suggest a novel mechanism to oppose the respiratory depression caused by opioids. Abstract : Abstract figure legend Respiratory‐related muscles and their corresponding neural structures in the CNS. EMG activity of genioglossus, laryngeal, diaphragm and intercostal muscles elicited by cervical EES indicates that cervical EES probably activates central, medullary respiratory networks that in turn activate the hypoglossal nucleus, motor vagal nucleus, cervical spinal motor neurons at levels 3–6 (C3–C6), and thoracic spinal levels 1–11 (T1–T11), respectively. Deltoid EMG was recorded as a control for monitoring non‐respiratory‐related neural and motor activities at cervical spinal level 5 (C5).